Clinical presentation, hormonal profiles in nulliparous Korean women with polycystic ovarian morphology - Y.J. Shin; S. Lee; J.E. Lee; S. Won; M.J. Kim (IMR Press, 2020)
Purpose: The aim of this study was to determine the relationship between polycystic ovarian morphology (PCOM), ovarian morphology, anti-Müllerian hormone (AMH), and testosterone levels in young nulliparous Korean women. Materials and Methods: A total of 139 PCOM patients were evaluated from 2013 to 2018. The relationships between serum AMH levels and androgenic hormones, clinical signs of polycystic ovarian syndrome (PCOS), and ovarian morphology were investigated. Results: Irregular menstruation was the most common symptom in women with PCOM. This study found that hyperandrogenism was present in 26.6% of nulliparous Korean women with PCOM. The present findings support the use of serum AMH as a useful marker to reflect PCOM in cases where accurate ultrasounds are not available. Conclusions: This study found that PCOM did not equate with PCOS, although PCOM is one of the diagnostic criteria for PCOS. AMH levels were positively correlated with ovarian volume and AMH levels were not reflected by hyperandrogenism. Content: The use of serum AMH as a useful marker to reflect PCOM in cases where accurate ultrasounds are not available.